(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2020)
This study aims to assess the impact of climate change on monthly rates for minimum temperature for the winter months in Misrata Area, by analysing the monthly averages of data from 1970-2010, to see the general trend, of the minimum temperature during the last 40 years, using a variety of statistical methods, including: simple linear regression, t- test, and the results of the study showed that trends for the increase in monthly rates for lesser temperature for winter Misrata Area at the level of statistical significance is less than 0.05.